Method for cost-effective trans aortic valve replacement device prototyping - Angelique Oncale; Charles Taylor; Erika Louvier; G. H. Massiha (Institute of Advanced Engineering and Science, 2020)
Trans Aortic Valve Replacement (TAVR) has offered the cardiology sector of health a new alternative to open heart surgeries which treat aortic stenosis. The technologies used by TAVR manufacturers are kept private. Our research goal was to develop a process that allows college level laboratories to fabricate their own TAVR stents in order to research new designs and methods of fabrication which may improve current TAVR practices. By creating a solid model of a stent cell design in SolidWorks, we were able to export a cutting pattern we used with a waterjet. The stent frame was then hand polished to prepare for fabric skirting and leaflet attachment. Synthetic ripstop fabric was cut using a commercial fabric cutting machine and attached to the frame using a waterproof glue. Future research entails welding techniques, improved polishing methods, and implantation into a mechanical system. This prototype could be used for TAVR related research and surgical training simulations.